2013
DOI: 10.5430/jhm.v3n1p18
|View full text |Cite
|
Sign up to set email alerts
|

Long term use of curcumin in two smoldering multiple myeloma patients

Abstract: Introduction: Smoldering Multiple Myeloma (SMM) is an asymptomatic plasma cell disorder which has an overall risk of progression to multiple myeloma of 10% per year. The cornerstone of managing SMM is a "watch and wait" strategy. Curcumin has been shown to improve disease status in some patients with MGUS and SMM and has been added to the mainstream treatment of myeloma patients. We report here for the first time on long term use of oral curcumin in 2 SMM patients.Patients: Two male Caucasian patients over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Previous studies carried out in our clinics have demonstrated that oral administration of curcumin, even at high doses (up to 8 g daily), is well tolerated and can decrease the paraprotein load, free light chains, bone turnover, and % plasma cell dyscrasia in a selected group of patients with multiple myeloma precursor disease that is monoclonal gammopathy of undetermined significance (MGUS) and smoldering multiple myeloma (SMM) …”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies carried out in our clinics have demonstrated that oral administration of curcumin, even at high doses (up to 8 g daily), is well tolerated and can decrease the paraprotein load, free light chains, bone turnover, and % plasma cell dyscrasia in a selected group of patients with multiple myeloma precursor disease that is monoclonal gammopathy of undetermined significance (MGUS) and smoldering multiple myeloma (SMM) …”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Previous studies carried out in our clinics have demonstrated that oral administration of curcumin, even at high doses (up to 8 g daily), is well tolerated and can decrease the paraprotein load, free light chains, bone turnover, and % plasma cell dyscrasia in a selected group of patients with multiple myeloma precursor disease that is monoclonal gammopathy of undetermined significance (MGUS) and smoldering multiple myeloma (SMM). [20][21][22][23] The multitude of published studies, including an in vitro study carried out in our laboratory, 16 suggest that curcumin can potentiate not only the cytotoxic effect of multiple agents used in the treatment of MM, but also enhance the chemo-sensitizing effects of these agents. The implications arising from these observations may be of important clinical benefit: i) curcumin studies can be designed to assess the additive antimyeloma effects of curcumin to the current treatment protocols and ii) curcumin may be used as an alternative to corticosteroids in such protocols.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Based on these antimyeloma effects of curcumin in vitro and the fact that this nonnutritive phytochemical is pharmacologically safe, even 14,15 clinical studies were carried out at St George Hospital and Southern Sydney Haematology, Kogarah, Sydney from 2010 until 2015 and found that curcumin decreases paraprotein load, bone turnover, free light chains and % plasma cells in the bone marrow of some MGUS and SMM patients. [16][17][18][19] In addition, based on the demonstrable effects of curcumin in MGUS and SMM, curcumin was administered to a patient with IgG lambda SMM with supraglottic AL amyloidosis. Immunoglobulin light chain amyloidosis (AL) along with MM, SMM, and MGUS represent a spectrum of plasma cell dyscrasias (PCDs).…”
mentioning
confidence: 99%
“…Recent clinical studies have demonstrated that oral administration of curcumin, even at high doses, is well tolerated and can decrease the paraprotein load, free light chains, bone turnover and % plasma cell infiltrate into the bone marrow in some patients with monoclonal gammopathy of undetermined significance (MGUS) and smoldering multiple myeloma (SMM) [12][13][14][15] .…”
mentioning
confidence: 99%